2019
DOI: 10.1155/2019/8717694
|View full text |Cite
|
Sign up to set email alerts
|

CD73 Expression on Mesenchymal Stem Cells Dictates the Reparative Properties via Its Anti-Inflammatory Activity

Abstract: Mesenchymal stem cells (MSC) are not universal and may be subject to dynamic changes upon local milieus in vivo and after isolation and cultivation in vitro. Here, we demonstrate that MSC derived from murine pericardial adipose tissue (pMSC) constitute two cohorts of population distinguished by the level of CD73 expression (termed as CD73high and CD73low pMSC). Transplantation of two types of cells into mouse hearts after myocardial infarction (MI) revealed that the CD73high pMSC preferentially brought about s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
(45 reference statements)
0
42
0
Order By: Relevance
“…Interestingly, flow cytometry analysis of the 2D cultures revealed an increase in CD73 mean fluorescence intensity, in both inflamed BMMSCs and CPSCs. Tan et al observed that the presence of a subpopulation of MSCs with increased CD73 expression was associated with better cardiac repair, as a result of involvement in the regulation of local immune response through purinergic signaling 49 . In addition, they demonstrated that this high CD73-expressing MSC population was able to recruit CD11b+/CCR2+ macrophages with an anti-inflammatory profile.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, flow cytometry analysis of the 2D cultures revealed an increase in CD73 mean fluorescence intensity, in both inflamed BMMSCs and CPSCs. Tan et al observed that the presence of a subpopulation of MSCs with increased CD73 expression was associated with better cardiac repair, as a result of involvement in the regulation of local immune response through purinergic signaling 49 . In addition, they demonstrated that this high CD73-expressing MSC population was able to recruit CD11b+/CCR2+ macrophages with an anti-inflammatory profile.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity in CD73 expression and its catalytic products may have distinct modulatory effects on the local immune response. This statement may explain the differences observed during tissue regenerative cell-based therapy (Tan et al, 2019).…”
Section: Regulation Of Metabolic Pathwaysmentioning
confidence: 81%
“…into distinct subsets of tissue macrophages (M1/M2) and function synergistically, but at times counteractively, with other cellular components in a reparative process, orchestrated mainly by the local milieu and cytokine profile (7,8).…”
Section: Ctrp3 Induces An Intermediate Switch Of Cd14 ++ Cd16 + Monocmentioning
confidence: 99%
“…RT-qPCR was performed to determine the mRNA expression levels of IL-6 and TNF-α following the pharmacological treatments. Total RNA of monocytes was isolated using the RNeasy Micro Kit (Qiagen) and complementary DNA was synthesized using the QuantiTect Reverse Transcription Kit (Qiagen) according to the manufacturer's protocol and as previously described (8). The thermocycling conditions were as follows: Initial denaturation for 2 min at 50˚C, and 40 cycles of 10 min at 95˚C and 1.5 min at 60˚C.…”
Section: Assessment Of Phagocytic and Migratory Activitymentioning
confidence: 99%
See 1 more Smart Citation